2020
DOI: 10.1159/000508930
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Esophagitis in a Patient with Oral Carcinoma and Bone Metastasis

Abstract: Radiation esophagitis requiring endoscopic evaluation occurs quite rarely, affecting <1% of patients undergoing radiation treatment. Acute radiation esophagitis develops within 3 weeks of radiation therapy. We describe herein a case of radiation esophagitis in a patient with oral carcinoma with multiple general bone metastases. Cisplatin, fluorouracil, and cetuximab were given for 3 cycles. Radiation therapy (30 Gy) to the thoracic vertebrae and lumbar vertebrae was prescribed to prevent worsening of bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“… 37 , 38 , 39 , 40 In the palliative setting, only 1 case has reported a grade 3 esophagitis when fluorouracil/cisplatin and cetuximab were combined with 30 Gy in 10 fr spine RT. 41 A retrospective study reported no CTCAE grade 3 or higher toxicity 42 when hypofractionated RT was used in 3 patients with metastatic head and neck cancer. 42 Other studies reporting head and neck SBRT delivered concomitantly with cetuximab were in recurrent settings.…”
Section: Resultsmentioning
confidence: 98%
“… 37 , 38 , 39 , 40 In the palliative setting, only 1 case has reported a grade 3 esophagitis when fluorouracil/cisplatin and cetuximab were combined with 30 Gy in 10 fr spine RT. 41 A retrospective study reported no CTCAE grade 3 or higher toxicity 42 when hypofractionated RT was used in 3 patients with metastatic head and neck cancer. 42 Other studies reporting head and neck SBRT delivered concomitantly with cetuximab were in recurrent settings.…”
Section: Resultsmentioning
confidence: 98%
“…Профилактику развития ЛЭ обеспечивают коррекция диеты пациента (механически и химически щадящая диета), прием ингибиторов протонной помпы. Для лечения острого ЛЭ используют препараты для восстановления слизистой, анальгетики [16].…”
Section: лэ и энтеритunclassified